KOMUNIKASI TRANSENDENTAL DALAM SENI KALIGRAFI ISLAM DI SANGGAR AL-FATH TANJUNG KURAS KECAMATAN SUNGAI APIT KABUPATEN SIAK - Eka Sri Melati; Yusuf Afandi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the implementation of transcendental communication in the art of Islamic calligraphy at Sanggar Al-Fath Tanjung Kuras. In Islam, every work of art is another form of worship (as a form of devotion to Allah Subhanahu Wa Ta'ala), moreover the art that is made is the art of calligraphy which contains verses of the Qur'an, in addition to writing the khattat also reading the meaning of the verse so that the message is conveyed clearly. The artistic value of calligraphy is found in how khattat presents implied meanings directly to the mind. This is evidenced by the way calligraphy conveys sacred messages from the verses of the Qur'an. This study uses a qualitative method with a descriptive approach. The results of this study, the researchers found several elements that include transcendental communication, namely the communicator (Allah), the communicant (khattat), the message (the verses of the Qur'an which are usually written by khattat in the Al-Fath Studio, including: Lafadz Basmalah, QS. Al-'Alaq 1-5, QS. Al-Ikhlas, QS. Al-Insyirah, QS. Ali-Imran 119), channel (calligraphy writing written by khattat in Al-Fath Studio Tanjung Kuras), results (facilitates the khattats in memorizing the Qur'an, increasing the love of the Qur'an and training the patience of the khattats, besides that it can also increase the talent of the khattat Al-Fath Studio for the art of Islamic calligraphy) and feedback (calm and patience too) felt when writing divine messages). Therefore, Islamic calligraphy is used as a form of worship by khattat to get closer to Allah by reading and writing verses of the Qur'an and understanding every message written. Keywords: Transcendental Communication, Islamic Calligraphy